88 National confidential enquiry into patient outcome and death in patients admitted with heart failure: a quality improvement project to improve compliance with recommendations. (17th July 2020) - Hayward, Carl; Mouyis, Kyriacos; Gillott, Holly; Adasuriya, Gamith; Ng, Sher May; Harvey, George; Akhtar, Mohammed Abid; Mohammad, Hira; Sotto, Imelda; Lee, Lok Yee; Toma, Tania; Harding, Daniel; et al.
Abstract : Introduction: Patients admitted with decompensated heart failure have a high risk of mortality and morbidity. Recommendations in a recent report from the National Confidential Enquiry into Patient Outcome and Death (NCEPOD), 2018, are designed to improve the management of these patients. Aim: We conducted a quality improvement project (QIP) to improve compliance with recommendations from the NCEPOD report. Methods: The NCEPOD report recommends that the following information be recorded for patients admitted with heart failure: a named healthcare coordinator, diagnosis, aetiology, current medications, self-management guidance, functional ability, social needs and a referral to cardiac rehabilitation. We reviewed the notes of patients who were coded to have a primary diagnosis of heart failure. We excluded patients who died during the admission, or those we felt were incorrectly coded. The outcome measure was the proportion of heart failure admissions in which the NCEPOD recommended data were recorded. We recorded baseline data for all admissions in 2018 and then implemented four interventions throughout 2019. The following interventions were implemented; 1. education for junior doctors, 2. a template was created for discharge summaries, 3. a separate discharge form was created and completed by the by heart failure clinical nurse specialists (CNS) that linked data from Microsoft Access to create a word document, 4. a template electronic document was created to facilitate a simple referral to cardiac rehabilitation. Results: The results are summarised in Table 1 . At baseline, the majority of factors were poorly recorded except for medications and diagnosis. The effect of each intervention can be seen in Table 1 . Conclusions: The baseline data suggested poor compliance with the NCEPOD recommendations. This may be anticipated given that these data preceded the recommendations. To establish improvements, reliance on junior doctors had some effect in improving adherence, but required constant reinforcement. A more effective intervention was to rely on the heart failure CNS which provided more continuity, they had more buy-in and through their knowledge of the patients the data could be completed quickly and reliably. These interventions allowed more information to be conveyed to general practice and other healthcare professionals caring for the patients. Conflict of Interest: Nil